Boo on the loose - Herman, Gail 1959-; Campbell, Brooks; Norman, Floyd; Tilley, Scott; Disney Enterprises (1996- ); Pixar (Firm) (New York Random House, 2012)
The number one Scare Team at Monsters, Inc., must come up with a solution when a girl named Boo makes her way onto the scare floor
"Over 30 stickers!"--Cover
"This work was originally published in different form as Boo on the loose, by Random House Children's Books in 2002."
At head of title: Disney Pixar Monsters, Inc
English Stories
Accelerated Reader 1.4
Accelerated Reader
Keywords: Monsters -- Juvenile fiction; Monsters -- Fiction; Readers; Fiction -- Monsters; Monsters; Children's stories; Readers; Fiction; Juvenile works; Movie novels; Readers (Elementary); Readers (Publications); Readers (Publications); Readers; readers